The Role of Education in Political Socialization of the Nigerian Citizens: Implication For Primary Education - Ann Ngozi Ugobueze (Action Research Journal Indonesia (ARJI), 2024)
Education, especially at the primary level, serves as the foundation for instilling democratic values, civic responsibility, and political awareness. This study used a survey research design to examine the role of education in political socialization in Aguata Local Government Area. A sample of 100 participants from selected communities was surveyed using a structured questionnaire with a four-point Likert scale. Data analysis applied a 2.5 mean cutoff for acceptance. The findings reveal that primary education significantly contributes to the political socialization of children, equipping them with the necessary knowledge and skills to understand political systems and engage in democratic processes. Key elements such as political education in schools, exposure to mass media, and participation in civic activities were identified as critical factors in shaping political dispositions. However, the study also highlights challenges such as inadequate political education, limited resources, and the need for curriculum reforms to foster a more inclusive and effective political socialization process. The study highlights the importance of integrating comprehensive civic education into primary school curricula to promote national unity, enhance political engagement, and prepare young Nigerians to become responsible, active citizens. The findings suggest that strengthening political socialization at the primary education level is vital for ensuring the development of a politically conscious and participatory citizenry, which is essential for the sustainable growth of Nigeria’s democracy